Reference intervals for radiographic, echocardiographic and N-terminal pro B-type natriuretic peptide values in healthy kittens. Issue 4 (April 2021) - Gunther-Harrington, Catherine T; Sharpe, Ashley N; Vernau, Karen M; Ueda, Yu; Montgomery, Elizabeth A; Surmick, Jennifer D; Fernandez, Nicole; Ontiveros, Eric; Walker, Ashley L; Stern, Joshua A
Objectives: Assessment of heart size in kittens is important, and there is a need for reference intervals (RIs) to prevent misinterpretation of cardiomegaly in this patient population. The purpose of this study was to generate RIs for echocardiographic and radiographic quantification of cardiac size in healthy kittens. Methods: In total, 88 kittens aged 6–16 weeks were enrolled in this study. Physical examination, and radiographic and echocardiographic evaluations were performed without sedation. Thoracic radiographs and echocardiographic images were measured to establish RIs for vertebral heart score (VHS), cardiac thoracic ratio (CTR) and multiple echocardiographic variables. N-terminal pro B-type natriuretic peptide (NT-proBNP) was measured. Statistical correlations between echocardiographic parameters and age, body weight and sex were all evaluated and RIs were generated. Results: Low-grade heart murmurs were appreciated in 26/88 kittens (29.5%). Kittens had a median VHS of 9.5 vertebrae (95% RI 8.0–10.9) and a median CTR of 67.2% (95% RI 54.4–79.8%). Measured NT-proBNP levels were comparable to healthy adult cats with a median of 31 pmol/l (upper reference limit 75 pmol/l). Multiple moderate-to-strong correlations between body weight and age with various echocardiographic parameters were observed and allometric scaling was performed for body weight. RIs for echocardiographic parameters were generated based on patient weight using allometric scaling formulas. Tricuspid valve regurgitation was a common finding and was present in 37.5% (n = 33) of the kittens. Conclusions and relevance: This study establishes RIs for thoracic radiograph assessment, echocardiography and cardiac biomarkers in kittens, which fills a critical gap in the veterinary literature. The VHS reported in this study is higher than previously reported for adult cats.